Anti-HMGCR myopathy may resemble limb-girdle muscular dystrophy. Issue 1 (January 2019) - Mohassel, Payam; Landon-Cardinal, Océane; Foley, A. Reghan; Donkervoort, Sandra; Pak, Katherine S.; Wahl, Colleen; Shebert, Robert T.; Harper, Amy; Fequiere, Pierre; Meriggioli, Matthew; Toro, Camilo; Drachman, Daniel; et al.
Abstract : Objective: To determine the prevalence and clinical features of anti-HMGCR myopathy among patients with presumed limb-girdle muscular dystrophy (LGMD) in whom genetic testing has failed to elucidate causative mutations. Methods: Patients with presumed LGMD and unrevealing genetic testing were selected based on a few clinico-pathologic features and tested for anti-HMGCR autoantibodies (n = 11). These clinico-pathologic features are peak creatine kinase (CK) greater than 1, 000 IU/L and at least 3 of the following features: (1) limb-girdle pattern of weakness, (2) selective involvement of posterior thigh on clinical examination or muscle imaging, (3) dystrophic changes on muscle biopsy, and (4) no family history of muscular dystrophy. Results: Six patients tested positive for anti-HMGCR autoantibodies. In 4, there was a presymptomatic phase, lasting as long as 10 years, characterized by elevated CK levels without weakness. Muscle biopsies revealed variable degrees of a dystrophic pathology without prominent inflammation. In an independent cohort of patients with anti-HMGCR myopathy, 17 of 51 (∼33%) patients were initially presumed to have a form of LGMD based on clinico-pathologic features but were ultimately found to have anti-HMGCR myopathy. Most of these patients responded favorably to immunomodulatory therapies, evidenced by reduction of CK levels and improved strength. Conclusions: Anti-HMGCR myopathy can resemble LGMD. Diagnosis of patients with a LGMD-like presentation of anti-HMGCR myopathy is critical because these patients may respond favorably to immunotherapy, especially those with shorter disease duration.